2016
DOI: 10.1155/2016/8324826
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of Catalysts for Removal of Volatile Organic Compounds in Flue Gas by Combustion: A Review

Abstract: Volatile organic compounds (VOCs) emitted from anthropogenic sources pose direct and indirect hazards to both atmospheric environment and human health due to their contribution to the formation of photochemical smog and potential toxicity including carcinogenicity. Therefore, to abate VOCs emission, the catalytic oxidation process has been extensively studied in laboratories and widely applied in various industries. This report is mainly focused on the benzene, toluene, ethylbenzene, and xylene (BTEX) with add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 97 publications
0
53
0
Order By: Relevance
“…The most commonly studied metal oxide catalysts include Co- [5,[22][23][24][25], Cu- [5,22,26], Mn- [5,22,25], Ce- [5,12,16,26], and Fe-containing materials [21,22]. It has been found that a suitable chosen support with controlled porosity favors high dispersion of active phase and enhanced activity in the total oxidation of VOCs [27][28]. From this point of view, zeolites can be expected as interesting supports of metal oxide species for the abatement of relatively small organic molecules, which can enter and migrate through channels present in the structure of these materials [13-15, 21-22, 29-30].…”
mentioning
confidence: 99%
“…The most commonly studied metal oxide catalysts include Co- [5,[22][23][24][25], Cu- [5,22,26], Mn- [5,22,25], Ce- [5,12,16,26], and Fe-containing materials [21,22]. It has been found that a suitable chosen support with controlled porosity favors high dispersion of active phase and enhanced activity in the total oxidation of VOCs [27][28]. From this point of view, zeolites can be expected as interesting supports of metal oxide species for the abatement of relatively small organic molecules, which can enter and migrate through channels present in the structure of these materials [13-15, 21-22, 29-30].…”
mentioning
confidence: 99%
“…These results indicate that the internal structure of the natural diatomite was partially hollow, with internal voids of irregular shapes and broad size distribution. A significant decrease in the quantity of N 2 adsorbed by the samples with the increase of the deposited metal load was also observed (Figure 3a), which was associated with the formation of metal particles in the support's porous structure, causing the complete or partial occlusion of some of the pores [9]. A typical isotherm of pure silica (type II isotherm) was observed during the N 2 physisorption analysis of food-grade diatomite (Figure 3b) [46].…”
Section: Morphological and Textural Analysismentioning
confidence: 85%
“…Aggregates of similar morphology but larger size were also observed on Mn 10 Co 15 /F, as shown in Figure 2l. The formation of larger aggregates observed on Mn 10 Co 15 /F might be related to the lower specific surface area of this support as the higher density of metal particles on the support surface might promote the formation of larger aggregates [9,63]. Figure 9.…”
Section: Characterization Of the Used Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the process, catalytic components can be added to promote both adsorption and incineration, and the process steps are integrated into a single reactor. In the integrated catalytic/adsorption process, fixed bed reactors containing catalytic adsorbents are employed to continuously adsorb VOCs from the effluents in one bed and convert VOCs on the catalytic adsorbent into benign carbon dioxide and water in the other [5][6][7]. Compared with the conventional adsorber-incinerator, the system is relatively simple, high in VOC removal efficiency, and low in operation and maintenance cost.…”
Section: Introductionmentioning
confidence: 99%